Горячий ключ: роман / И. А. Мельникова - Мельникова Ирина Александровна (Незнакомка, 2011)
Экземпляры: ф.10 (2012) / Инвентарный номер: 54474 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 48 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44